ANALISIS PERBEDAAN RETURN DAN RISIKO SAHAM PORTOFOLIO OPTIMAL DENGAN BUKAN PORTOFOLIO OPTIMAL - Pardosi, Bernanto; Wijayanto, Andhi (Management Analysis Journal, 2015)
The aim of this study is to find out if there are any differences of return and risk between optimal portfolio candidate and non-optimal portfolio candidate. This is a quantitative study with purposive sampling technique. Population of this study is all data of IDX 30 index which is 42 whereas the sample is 15. Analysis model that is used in this study is Markowitz method. The results of calculations using the Markowitz methods that includes the optimal portfolio with the proportion of funds that of UNVR stock as 31.19%, BBCA stock as 16.69%, ADRO stock as 14.14%, UNTR stock as 13.43%, PGAS stock as 9.33%, INDF stock as 7.73% and GGRM stock as 7.50%. The conclusion of this study is that there are no significant differences of return and risk on the formation of optimal portfolio. This shows that the preferences of investors do not consider the calculation methods Markowitz and indifference curve in selecting the optimal portfolio. Suggestion related to this study is that investor and investment manager may execute the investment fund to form an optimal portfolio Markowitz method as a benefit from stock diversification